The effect of the digital printing of fabric on the morphology of passive bloodstains - Dicken, Lisa; Knock, Clare; Carr, Debra J.; Beckett, Sophie (Elsevier, 2022)
Bloodstained fabrics found at crime scenes are likely to have had processing treatments, such as dyeing or printing, but the effect of the treatments on bloodstain morphology is not always considered. In order to study the effect of digital printing on bloodstain morphology, drip stains were created from five impact velocities (1.9–5.4 ms−1) on three different mass per unit areas (88–226 g/m²) of 100% cotton calico which had been digitally printed using reactive dye. Across all three printed fabrics, the bloodstains appeared visually similar, and no correlation was found between the dry bloodstain area and the impact velocity. When comparing the bloodstains on the printed fabric to those which had been created previously on the same fabric in a dyed and not-coloured state, the dry bloodstains on the printed fabric were statistically significantly larger (e.g. for the calico with the lightest mass per unit area, mean dry bloodstain area was 126.6, 64.4 and 44.3 mm² for the printed, dyed and not-coloured fabrics respectively). Examination of the larger bloodstains on the printed calico with the micro computed tomography scanner and scanning electron microscope, suggested that the printing process increased the wettability of the fabric, so the blood could spread more easily on the surface. This allowed the blood to coat the yarns, and wick into them before wicking along the intra-yarn spaces. The results presented in this paper showed that care must be taken when examining bloodstains at crime scenes. Depending on the fabric and the processing of the fabric the size of the blood stains may not increase with impact velocity as wicking may result in a larger bloodstain from a lower velocity. The bloodstain on the penetrated face of the fabric may be larger than on the impacted face and the same fabrics with different processing will produce different blood stain sizes and shapes.
Keywords: Bloodstain analysis; Absorbent surfaces; Wicking; Wetting